Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Sure, let's find the inverse functions for each given function and verify them by composition.
### Function [tex]\( f(x) = -2x + 3 \)[/tex]
1. Find the inverse function:
To find the inverse function, we start by replacing [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = -2x + 3 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ y - 3 = -2x \implies x = \frac{3 - y}{2} \][/tex]
Replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] to get the inverse function:
[tex]\[ f^{-1}(x) = \frac{3 - x}{2} \][/tex]
2. Verify by composition:
To verify that [tex]\( f^{-1}(x) \)[/tex] is indeed the inverse of [tex]\( f(x) \)[/tex], we need to check that:
[tex]\[ f(f^{-1}(x)) = x \quad \text{and} \quad f^{-1}(f(x)) = x \][/tex]
- Verify [tex]\( f(f^{-1}(x)) \)[/tex]:
[tex]\[ f\left( f^{-1}(x) \right) = f\left( \frac{3 - x}{2} \right) = -2 \left( \frac{3 - x}{2} \right) + 3 = - (3 - x) + 3 = x \][/tex]
- Verify [tex]\( f^{-1}(f(x)) \)[/tex]:
[tex]\[ f^{-1}(f(x)) = f^{-1}(-2x + 3) = \frac{3 - (-2x + 3)}{2} = \frac{3 + 2x - 3}{2} = x \][/tex]
3. Graph:
To graph both [tex]\( f(x) \)[/tex] and [tex]\( f^{-1}(x) \)[/tex], plot the lines:
[tex]\[ f(x) = -2x + 3 \quad \text{and} \quad f^{-1}(x) = \frac{3 - x}{2} \][/tex]
The line [tex]\( y = x \)[/tex] will also be plotted as a reference as it represents the reflection line for the inverse functions.
### Function [tex]\( f(x) = 2x - 3 \)[/tex]
1. Find the inverse function:
Replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = 2x - 3 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ y + 3 = 2x \implies x = \frac{y + 3}{2} \][/tex]
Replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] to get the inverse function:
[tex]\[ f^{-1}(x) = \frac{x + 3}{2} \][/tex]
2. Verify by composition:
To verify that [tex]\( f^{-1}(x) \)[/tex] is indeed the inverse of [tex]\( f(x) \)[/tex], we need to check that:
[tex]\[ f(f^{-1}(x)) = x \quad \text{and} \quad f^{-1}(f(x)) = x \][/tex]
- Verify [tex]\( f(f^{-1}(x)) \)[/tex]:
[tex]\[ f\left( f^{-1}(x) \right) = f\left( \frac{x + 3}{2} \right) = 2 \left( \frac{x + 3}{2} \right) - 3 = x + 3 - 3 = x \][/tex]
- Verify [tex]\( f^{-1}(f(x)) \)[/tex]:
[tex]\[ f^{-1}(f(x)) = f^{-1}(2x - 3) = \frac{(2x - 3) + 3}{2} = \frac{2x}{2} = x \][/tex]
3. Graph:
To graph both [tex]\( f(x) \)[/tex] and [tex]\( f^{-1}(x) \)[/tex], plot the lines:
[tex]\[ f(x) = 2x - 3 \quad \text{and} \quad f^{-1}(x) = \frac{x + 3}{2} \][/tex]
Again, the line [tex]\( y = x \)[/tex] will be plotted as a reference.
These steps provide clear guidance on finding the inverse functions for [tex]\( f(x) = -2x + 3 \)[/tex] and [tex]\( f(x) = 2x - 3 \)[/tex], verifying them through composition, and graphing the functions along with their inverses.
### Function [tex]\( f(x) = -2x + 3 \)[/tex]
1. Find the inverse function:
To find the inverse function, we start by replacing [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = -2x + 3 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ y - 3 = -2x \implies x = \frac{3 - y}{2} \][/tex]
Replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] to get the inverse function:
[tex]\[ f^{-1}(x) = \frac{3 - x}{2} \][/tex]
2. Verify by composition:
To verify that [tex]\( f^{-1}(x) \)[/tex] is indeed the inverse of [tex]\( f(x) \)[/tex], we need to check that:
[tex]\[ f(f^{-1}(x)) = x \quad \text{and} \quad f^{-1}(f(x)) = x \][/tex]
- Verify [tex]\( f(f^{-1}(x)) \)[/tex]:
[tex]\[ f\left( f^{-1}(x) \right) = f\left( \frac{3 - x}{2} \right) = -2 \left( \frac{3 - x}{2} \right) + 3 = - (3 - x) + 3 = x \][/tex]
- Verify [tex]\( f^{-1}(f(x)) \)[/tex]:
[tex]\[ f^{-1}(f(x)) = f^{-1}(-2x + 3) = \frac{3 - (-2x + 3)}{2} = \frac{3 + 2x - 3}{2} = x \][/tex]
3. Graph:
To graph both [tex]\( f(x) \)[/tex] and [tex]\( f^{-1}(x) \)[/tex], plot the lines:
[tex]\[ f(x) = -2x + 3 \quad \text{and} \quad f^{-1}(x) = \frac{3 - x}{2} \][/tex]
The line [tex]\( y = x \)[/tex] will also be plotted as a reference as it represents the reflection line for the inverse functions.
### Function [tex]\( f(x) = 2x - 3 \)[/tex]
1. Find the inverse function:
Replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = 2x - 3 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ y + 3 = 2x \implies x = \frac{y + 3}{2} \][/tex]
Replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] to get the inverse function:
[tex]\[ f^{-1}(x) = \frac{x + 3}{2} \][/tex]
2. Verify by composition:
To verify that [tex]\( f^{-1}(x) \)[/tex] is indeed the inverse of [tex]\( f(x) \)[/tex], we need to check that:
[tex]\[ f(f^{-1}(x)) = x \quad \text{and} \quad f^{-1}(f(x)) = x \][/tex]
- Verify [tex]\( f(f^{-1}(x)) \)[/tex]:
[tex]\[ f\left( f^{-1}(x) \right) = f\left( \frac{x + 3}{2} \right) = 2 \left( \frac{x + 3}{2} \right) - 3 = x + 3 - 3 = x \][/tex]
- Verify [tex]\( f^{-1}(f(x)) \)[/tex]:
[tex]\[ f^{-1}(f(x)) = f^{-1}(2x - 3) = \frac{(2x - 3) + 3}{2} = \frac{2x}{2} = x \][/tex]
3. Graph:
To graph both [tex]\( f(x) \)[/tex] and [tex]\( f^{-1}(x) \)[/tex], plot the lines:
[tex]\[ f(x) = 2x - 3 \quad \text{and} \quad f^{-1}(x) = \frac{x + 3}{2} \][/tex]
Again, the line [tex]\( y = x \)[/tex] will be plotted as a reference.
These steps provide clear guidance on finding the inverse functions for [tex]\( f(x) = -2x + 3 \)[/tex] and [tex]\( f(x) = 2x - 3 \)[/tex], verifying them through composition, and graphing the functions along with their inverses.
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.